Fire Risk Level Mapping in Tanah Abang, Central Jakarta Using Geographic Information Systems (GIS) - Siti Nabilah Alzena; Juhadi Juhadi; Tjaturahono Budi Sanjoto (Universitas Lambung Mangkurat, 2025)
Rapid urbanisation has increased population density in Tanah Abang District, Jakarta, posing considerable fire dangers. This study uses the Analytical Hierarchy Process (AHP) and Geographic Information System (GIS) to map fire risk levels in seven urban settlements. Three key components were examined: hazard, vulnerability, and capacity. Expert assessments determined the weight of each parameter, which was then spatially analysed using ArcGIS overlay techniques. According to the findings, the majority of locations are classified as moderate risk, particularly dense settlements with restricted road access. Petamburan Village is the most vulnerable due to high poverty rates and a big concentration of vulnerable groups, whereas Gelora Village is the least vulnerable due to lower population density and more organised land usage. Mitigation initiatives have already been implemented, including fire safety education, fire extinguisher training, the formation of volunteer groups, and the installation of hydrants and extinguishers in public buildings. These findings emphasise the need of building local capability and using GIS as a foundation for better fire risk reduction strategy.